Pollution Impact of MSW Landfill Leachate - Pariathamby, Agamuthu; S. H, Fauziah (Malaysian Journal of Science, 2005)
Improper disposal of Municipal Solid Waste (here after referred to MSW) into landfills not only creates a conducive environment for pests like flies, rats and others but also pollutes the ecosystem with the release of leachate. This study was conducted to analyze leachate characteristics and compare pollution intensity among three landfills of different level of urbanization namely urban landfill, sub-urban landfill and rural landfill. Leachate from Kundang landfill representing the urban type showed the highest COD value (6230 mg/l) among the three landfills. Both the rural type (Panchang Bedena landfill) and sub-urban type (Sungai Sedu landfill) have COD at 5060 mg/l and 170 mg/l, respectively. The pH ranged between 6.7 - 8 in all three landfills, whereas the TSS was 1.6 mg/l, 0.09 mg/L and 0.06 mg/l, at the rural, sub-urban and rural types, accordingly. In the urban landfill, the concentration of Cr, Cu, Pb, Zn, and Mg were 0.193 ppm, 0.003 ppm, 0.027 ppm, 0.06 ppm, and 4.25 ppm, respectively while Cr was not detected. The quantum of pollution from the released leachate to adjacent rivers was low with BOD value of 1 240 g/day, 670 g/day and 3 240 g/day from the urban, sub-urban and rural land fill, respectively. The concentration of metals, particularly Mg, was high which requires a proper wastewater treatment plant to be installed in order to prevent euthrophication in water bodies. Physical and chemical treatment would be the best option to reduce the pollution impact to the environment due to the low BOD to COD ratio (0.004 to 0.13) and the high metal content in the leachate.